Height, diameter and volume in function the stump for Abies religiosa in different regions of Mexico - Guzmán-Santiago, Juan Carlos; Vargas-Larreta, Benedicto; Aguirre-Calderón, Oscar Alberto; De los Santos-Posadas , Héctor Manuel; Gómez-Cárdenas , Martín; González-Cubas, Rigoberto; Rodríguez-Ortiz, Gerardo; Hernández-Aguilar, José Antonio; Bautista-Cruz , Angelina (BOSQUE, 2023)
Forest inventories are the sources of information for the volumetric quantification of trees; however, this is made difficult when it has been cut down and only the stump remains, and this is achieved by regression. The objective of this work was to fit models for the prediction of the normal diameter (dn), height (h) and volume (v) from the diameter of the stump for Abies religiosa in different regions of Mexico. 2,599 data were used to analyze the variables with their respective predictions. Models were selected using adjusted coefficients of determination, root mean square error, bias, and log-likelihood, as well as residual analyses. The generated goodness of fit indicates that the equations are reliable to be incorporated in the Forest Management Units, where the allometric expression was ideal to describe the normal diameter and height in some cases, in addition to Schumacher in its exponential version for the same. The end; while, for volume, Schumacher expression was considered relevant. It is the first work with these types of regressions for the species and they can be added to the growth equations and will be useful for the reconstruction of the tree after a felling event.